Bonding of steel bars in concrete: A systematic review of the literature. (March 2023) - Reis, E.D.; de Azevedo, R.C.; Christoforo, A.L.; Poggiali, F.S.J.; Bezerra, A.C.S.
Abstract: Reinforced concrete structures represent one of the most used structural systems in civil construction, and their good behavior is guaranteed by the joint work of concrete and steel called adherence. This paper aims to review the steel–concrete adherence as a function of the concrete type, the replacement or addition content, the tests, the bar diameter, the surface type, and the anchorage length, among other parameters. To achieve the proposed objective, the ProKnow-C methodology was applied to identify the most relevant publications from the last ten years, and a bibliography with 85 papers was selected. The outcomes showed well-consolidated conclusions and gaps about the topic to be further investigated. Considering these gaps, the need for extensive studies on steel bonding in recycled aggregate concrete and rubber concrete waste is highlighted, as they are effective in improving sustainability and reuse of materials, as well as in steel fiber reinforced concrete and concrete with carbon nanotubes, which present promising results but few works in the literature. Besides, the pull-out test was found to be the most appropriate for steel–concrete bonding studies, and the adhesion of thin steel bars requires further investigation.